APLIKASI KOPERASI SIMPAN PINJAM MENGGUNAKAN METODE BERORIENTASI OBJEK - Sopiah, Nyimas; Indriani, Poppy (Universitas Bina Darma, 2013)
Cooperative Teacher Junior High School 53 in Palembang, a cooperative which is engaged in the savings and loan services. Role in the activities of the cooperative system komputersasi immense benefits, which in faster data processing and in accordance with the expected goals. However, the cooperative teacher at Junior High School 53 in Palembang is conducting recording data on cooperatives is still as simple as how to record all the data using the book, so that with the increasing number of members as well as data to be processed it will have obstacles to manage data these, it is necessary for the existence of accounting information systems, computer-based cooperative teachers, which the system will be able to speed up the process of cooperative service teachers at junior High School 53 Palembang, the author will build cooperative information systems accounting teachers using programming languages PHP and MySQL use these applications are expected to help data processing teachers cooperative and easier to get information quickly and accurately. Keywords: Accounting Information Systems, Cooperatives, Savings and Loans, PHP, MySQL